2022
DOI: 10.1007/jhep05(2022)101
|View full text |Cite
|
Sign up to set email alerts
|

Divisor topologies of CICY 3-folds and their applications to phenomenology

Abstract: In this article, we present a classification for the divisor topologies of the projective complete intersection Calabi-Yau (pCICY) 3-folds realized as hypersurfaces in the product of complex projective spaces. There are 7890 such pCICYs of which 7820 are favorable, and can be subsequently useful for phenomenological purposes. To our surprise we find that the whole pCICY database results in only 11 (so-called coordinate) divisors (D) of distinct topology and we classify those surfaces with their possible deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 66 publications
(147 reference statements)
0
26
0
Order By: Relevance
“…In particular there are several rigid surface which satisfy unit Arithmetic genus condition and hence can be a priori suitable for generating non-perturbative superpotential effects. This properties of the divisors of THCYs is unlike the case with the other database consisting of pCICYs defined by some multi-hypersurface constraints in the product of P n 's for which no coordinate divisor was found to be rigid [20].…”
Section: Some Insights With Observationsmentioning
confidence: 68%
See 4 more Smart Citations
“…In particular there are several rigid surface which satisfy unit Arithmetic genus condition and hence can be a priori suitable for generating non-perturbative superpotential effects. This properties of the divisors of THCYs is unlike the case with the other database consisting of pCICYs defined by some multi-hypersurface constraints in the product of P n 's for which no coordinate divisor was found to be rigid [20].…”
Section: Some Insights With Observationsmentioning
confidence: 68%
“…In this context, let us also mention that the divisor topologies of all the pCICYs have been recently computed and classified in [20] which have subsequently helped in classifying the PFFVs in [21] where it has been observed that pCICYs of K3-fibred type have more number of PFFV as compared to those which are not K3-fibred, and thus verifying the claim of [70].…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations